Unusual giant cell tumor of the clivus: a case documentation and analysis - Raiyani, Jankrut J.; Patel, Avni M.; Shah, Dharita S.; Sharma, Tanushka; Patel, Nidhi (International Journal of Research in Medical Sciences, 2025)
Giant cell tumors (GCTs) primarily occur in the epiphyses of long bones and are generally considered histologically benign. However, they can be locally aggressive, with a high rate of local recurrence, and have the potential for distant metastasis. Primary GCT of the clivus is extremely rare and is often misdiagnosed as pituitary macroadenoma or clival chordoma, making treatment controversial. The present report describes the case of a 17-year-old male with GCT located in the skull base originating from the clivus, with the involvement of adjacent cranial nerves, which was successfully treated with trans-nasal trans-sphenoidal surgery. This report contributes to the limited literature regarding GCTs of the skull.